Define Intervention (The Biblical archaeology review, 2023)
What is "Dilmun"? 1. Desert oasis in Genesis 2. Mound that rose from the primordial waters 3. Island reserved for survivors of the Great Flood 4. Caravanserai on the Silk Road 5. Landing spot of Noah’s Ark Answer: (3) In the Epic of Gilgamesh, Dilmun is the island reserved for Utnapishtim and his wife, who […]